Republic of Armenia : Ex Post Assessment of Long-Term Program Engagement. (IMF Staff Country Reports; Country Report, 2005)
This paper presents an Ex Post Assessment of Long-Term Program Engagement for Armenia. The quality of program implementation was uneven at the early stages of IMF engagement, but it has improved in recent years. Implementation of some key structural reforms suffered delays, reflecting in part capacity constraints and at times insufficient ownership. Collaboration between the IMF and the World Bank has been good. The Bank has played a valuable role in facilitating the streamlining of conditionality under the Poverty Reduction and Growth Facility arrangement.